RAGE Expression and ROS Generation in Neurons: Differentiation versus Damage. (25th May 2016) - Piras, S.; Furfaro, A. L.; Domenicotti, C.; Traverso, N.; Marinari, U. M.; Pronzato, M. A.; Nitti, M.
Abstract : RAGE is a multiligand receptor able to bind advanced glycation end-products (AGEs), amphoterin, calgranulins, and amyloid-beta peptides, identified in many tissues and cells, including neurons. RAGE stimulation induces the generation of reactive oxygen species (ROS) mainly through the activity of NADPH oxidases. In neuronal cells, RAGE-induced ROS generation is able to favor cell survival and differentiation or to induce death through the imbalance of redox state. The dual nature of RAGE signaling in neurons depends not only on the intensity of RAGE activation but also on the ability of RAGE-bearing cells to adapt to ROS generation. In this review we highlight these aspects of RAGE signaling regulation in neuronal cells.